Association between ossification of the longitudinal ligament of the cervical spine and arteriosclerosis in the carotid artery - Oshima, Yasushi; Doi, Toru; Kato, So; Taniguchi, Yuki; Matsubayashi, Yoshitaka; Nakajima, Koji; Oguchi, Fumihiko; Oka, Hiroyuki; Hayashi, Naoto; Tanaka, Sakae (Scientific reports, 2020)
Although several risk factors have been reported for cervical ossification of the longitudinal ligament (OPLL), most evaluations made in the past were based on plain X-ray, not on computed tomography (CT) scan. In this study, we aimed to clarify novel risk factors for cervical OPLL in asymptomatic subjects undergoing CT scan as their routine medical checkups. A total of 1789 Japanese asymptomatic subjects who underwent CT scan for the whole body as their routine medical checkups were retrospectively reviewed. The medical checkup also included laboratory examinations, bone mineral status, and ultrasound of the carotid artery. As a result, cervical OPLL was seen in 120 subjects (6.7%). As we compared the demographic and clinical data between subjects with and without OPLL, OPLL group showed older age, higher proportion of male sex, higher BMI, higher incidence of hypertension, higher levels of blood HbA1c and triglyceride, and higher incidence of plaques in the carotid artery. A multivariate logistic regression analysis revealed that age (Odds ratio (OR):1.03), male sex (OR: 1.91), and the presence of plaque in the carotid artery (OR: 1.71) were risk factors for OPLL. To the best of our knowledge, this is the first report to reveal an association between OPLL and arteriosclerotic lesions.